The Tradition of Henna Night in the Hadrami Arab Community in Jakarta - Chairunnisa, Gina Aqila; Priyoyudanto, Febri (International Journal of Science and Society, 2024)
The Hadhrami Arab is a community comes from Hadhramaut, South Yemen, and they still practice their traditions, one of which is the henna night tradition. This is an Arab tradition that is usually observed at weddings. The bride do henna the night before the wedding ceremony in this tradition. The Hadhrami Arab community in Tanah Abang district Jakarta is the subject of this study. The objective of conducting this research was to help the community understand the context of the henna night by providing new information about how the henna night tradition is still practiced by the Arab Hadhrami community in Tanah Abang Jakarta. A qualitative descriptive approach, a literature review, and interviews were used in this study. In this study, data was collected by processing library data and data from direct interviews with sources using seven questions related to the existing problem formulation. This study addressed two issues: first, what is the role of henna night in the tradition of the Arab Hadhrami community in Tanah Abang, Jakarta; and second, how is henna night conducted among the Arab Hadhrami community in Tanah Abang, Jakarta.